Alleviation of the Cadmium Toxicity by Application of a Microbial Derived Compound, Ectoine - Orhan, Furkan; Parlak, Kadriye Uruç; Tabay, Dilruba; Bozarı, Sedat (Water, air, and soil pollution, 2023)
Heavy metals are natural components that are formed as a result of biotic activities, accumulate in the ecosystem because they cannot be biodegraded, and thus cause environmental stress. In this study, the alleviation effect of the ectoine, which is the subject of many studies, on cadmium (Cd) toxicity was tested. Ectoine is produced by various bacteria in response to osmotic stress. Many different properties of this compound have been proven and studies on these compounds are constantly increasing. In the current study, we determined that ectoine has not any detrimental effect on plant (wheat) germination rate, antioxidant enzyme levels, H 2 O 2 and malondialdehyde (MDA) contents. On the other hand, co-treatment of ectoine with Cd (110 ppm) significantly alleviated Cd toxicity [increased germination rate, antioxidant enzyme levels and genomic template stability (GTS) and decreased the content of H 2 O 2 and MDA]. The findings mentioned above reports for the first time that ectoine has an amelioration effect on Cd toxicity. The alleviation effect of ectoine might arise from its reactive oxygen scavenging (singlet oxygen and hydroxyl radical) traits and macromolecule (DNA and protein) protection properties through which it decreases water molecules around macromolecules. Novelty Statement The findings of this study report for the first time that ectoine has an amelioration effect on Cd toxicity. The amelioration effect of ectoine against toxicity of cadmium was demonstrated by evaluating germination ratio, random amplified polymorphic DNA, content of H 2 O 2 and MDA and antioxidant enzymes. The results of the study show that ectoine ameliorates the toxicity caused by cadmium in all the analysed parameters.